Effect of steel fiber distribution on the mechanical properties of UHPC caused by vehicle-bridge coupling vibration. (October 2022) - Wang, Shunfeng; Yu, Long; Yang, Fei; Xu, Linglin; Wu, Kai; De Schutter, Geert; Yang, Zhenghong
Abstract: With the acceleration of infrastructure construction, the risk of being exposed to vehicle-bridge coupling vibration is getting more common for the unhardened cementitious materials, which also intensifies the stress on the concrete and leads to the presence of micro-cracks at early age. In order to simulate vehicle-bridge coupling vibration in the actual construction sites, the properties and microstructure evolution of ultra-high performance concrete (UHPC) were evaluated systematically by fixing the specimens on an electric vibration table immediately after casting. The vibration parameters considered in this work involve the frequency and the amplitude according to the in-site monitor data. The heterogeneous distribution of air voids and steel fiber was determined by X-CT on cylindrical specimens with diameter of 70 mm and height of 100 mm quantitatively. In the early hydration, the position and distribution of steel fibers in the UHPC matrix could be able to move freely, which has significant impact on the mechanical properties. The compressive strength and drying shrinkage of UHPC specimens gradually increase with increasing the amplitude and frequency. However, a large amplitude and frequency would be detriment to the flexural and tensile strength due to changes in the angle and spatial distribution of steel fiber although the total porosity only varies slightly. Increasing amplitude and frequency promotes the presence of coarser air bubble and reduction of steel fibers inclination angle. This study is helpful for the design and application of UHPC in the actual construction sites, which could avoid the material failure during construction.